ANALISIS STRATEGI PENGEMBANGAN USAHA KERAJINAN TANGAN MASYARAKAT LOKAL DI KAMPUNG MUPURUKA KABUPATEN MIMIKA - Yahya Nusa; Theresia Kabarubun; Theresia Magdarike Kuum (CV. Adiba Aisha Amira, 2024)
This research aims to determine the strategy for developing local community handicraft businesses in Mupuruka village. and to determine business growth and take advantage of opportunities to achieve business improvement in the strategy for developing local community handicraft businesses in Mupuruka village. The method used in this research is descriptive. Namely to develop a Local Community Handicraft Business Development Strategy in Mupuruka Village, Mimika Regency. The SWOT analysis instrument from the research results of handicraft businesses such as carvings/carvings, woven/noken, stick plates can be carried out by procurement and promotion to customers to contribute to increasing community self-reliance to improve welfare and can become a quality of carving and woven craftsmen as a culture. local community.